Graphic design and architecture, a 20th century history a guide to type, image, symbol, and visual storytelling in the modern world - Poulin, Richard (Rockport Publishers, 2012)
"This innovative volume is the first to provide the design student, practitioner, and educator with an invaluable comprehensive reference of visual and narrative material that illustrates and evaluates the unique and important history surrounding graphic design and architecture. Graphic Design and Architecture, A 20th Century History closely examines the relationship between typography, image, symbolism, and the built environment by exploring principal themes, major technological developments, important manufacturers, and pioneering designers over the last 100 years. It is a complete resource that belongs on every designer's bookshelf"--